1994
DOI: 10.1210/jcem.79.5.7962333
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal and adrenal catheterization during adrenal suppression and gonadal stimulation in a patient with bilateral testicular tumors and congenital adrenal hyperplasia.

Abstract: We report the case of a patient with bilateral testicular tumors and congenital adrenal hyperplasia due to 21-hydroxylase deficiency. Catheterization of the left testicular and adrenal veins was performed. The presence of 11 beta-hydroxylated steroids in the spermatic veins confirmed the presence of testicular tumor secondary to adrenal rest cells. After adrenal suppression by dexamethasone combined with gonadal stimulation with hCG, a dramatic decrease in androgens and adrenal steroids was observed in the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…When no testicular biopsy is available, however, some characteristics, such as the bilateral presence of lesions, the location of the lesions adjacent to the mediastinum and the decrease in size to glucocorticoid therapy, can be helpful in differentiating between a (benign) adrenal rest tumour and a malignant testicular lesion [12,17,21]. Also, steroid measurements in serum from testicular vein sampling can indicate the presence of active adrenal rest tissue in the testis [12,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…When no testicular biopsy is available, however, some characteristics, such as the bilateral presence of lesions, the location of the lesions adjacent to the mediastinum and the decrease in size to glucocorticoid therapy, can be helpful in differentiating between a (benign) adrenal rest tumour and a malignant testicular lesion [12,17,21]. Also, steroid measurements in serum from testicular vein sampling can indicate the presence of active adrenal rest tissue in the testis [12,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Based on histological studies, TARTs have close resemblance to adrenocortical tissue [130,131]. Functional studies in patients with 21OHD have identified ACTH and angiotensin II (AII) receptors and expression of CYP11B1 and CYP11B2 adrenal specific enzymes [132][133][134][135][136]. Presence of ACTH and AII receptors in the TART tissue indicates hormone responsive tissue which can undergo hypertrophy and/or hyperplasia due to elevated ACTH (and/ or AII) levels [132,137,138].…”
Section: Testicular Adrenal Rest Tumorsmentioning
confidence: 99%
“…One of the most important and frequently detected complications and the leading cause of infertility in adult male CAH patients is the development of benign testicular tumours [5,6,7]. As a result of the morphological and functional resemblance with adrenal tissue they are usually referred to as 鈥榯esticular adrenal rest tumours' (TART) [8,9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%